2019
DOI: 10.1186/s12913-019-4338-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a community of practice for speech-language pathologists in aphasia rehabilitation: a logic analysis

Abstract: Background Aphasia is a communication disorder affecting participation. Although there are evidence-based practice recommendations about participation and aphasia rehabilitation, it may be challenging for speech-language pathologists to ensure that rehabilitation activities have an impact on the person’s participation, in part due to time limitations. Participation remains limited after rehabilitation for persons who have aphasia. Communities of practice (CoPs) are a collaborative knowledge transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…It is not clear from the studies explored in this review how the key ingredients of the ICAP are thought to complement each other. Reporting of a logic model is advised when developing and evaluating complex interventions [165] and there is emerging evidence of the use of logic models in the field of SLT [166]. Future research leading from this review will develop a logic model for ICAPs.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear from the studies explored in this review how the key ingredients of the ICAP are thought to complement each other. Reporting of a logic model is advised when developing and evaluating complex interventions [165] and there is emerging evidence of the use of logic models in the field of SLT [166]. Future research leading from this review will develop a logic model for ICAPs.…”
Section: Discussionmentioning
confidence: 99%
“…To address the issue of peer exchanges on matters pertaining to EBP, Rochette et al 58 suggested the use of professional networking to improve broader EBP competencies rather than targeting individual discrete skills. Communities of practice and mentorship by more seasoned professionals may also support professionals in this area once they enter practice 68‐70 …”
Section: Discussionmentioning
confidence: 99%
“…Communities of practice and mentorship by more seasoned professionals may also support professionals in this area once they enter practice. [68][69][70] When designing EBP curricula, OT and PT educators can implement multiple teaching methods and technologies such as mobile apps, simulation, and websites such as Stroke Engine (https://www. strokengine.ca).…”
Section: Associations Between Knowledge Attitudes As Well As Confidence and The Use Of Ebp And Eb Activitiesmentioning
confidence: 99%
“…Depending on mandate, datacollection sources could be broadened to include non-CoP members and better inform analysis of value generated at the organizational, external stakeholder, and field levels. Depending on resources, the primarily qualitative approach could be extended to mixed methods approaches, similar to that applied in evaluating a rehabilitation CoP (Gauvreau, Le Dorze, Kairy, & Croteau, 2019) and radiation treatment program CoP (Glicksman et al, 2019), or quantitative indicators can show the different types of value created and for whom. More mi cro-level tools can be used for data collection and analysis.…”
Section: Future Directions and Applicationsmentioning
confidence: 99%